2005
DOI: 10.1103/physrevlett.95.193902
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of the Oscillation Frequency in an Optical-Tweezers Trap by Parametric Excitation

Abstract: We demonstrate a novel technique for direct measurement of the oscillation frequency in an optical-tweezers trap. The technique uses the phenomenon of parametric resonance in an oscillator when the stiffness of the trapping potential is modulated. The trapped particle is a strongly damped oscillator; hence, the signature of parametric resonance is not an increase in the amplitude but an increase in the size of Brownian fluctuations. The trap frequency is measured with an accuracy of 0.1%, which is better than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…19 The output of the QPD was first sampled at 16 kHz for a total data length of 100,000 points. A fast Fourier transform of the data set gave its ͑complex͒ Fourier spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…19 The output of the QPD was first sampled at 16 kHz for a total data length of 100,000 points. A fast Fourier transform of the data set gave its ͑complex͒ Fourier spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of pumping mechanical energy into optically trapped particles could open the way to many applications. In optical tweezers, even though it is easy to periodically modulate the laser power, parametric excitation is usually ineffective because of the heavy damping action of the surrounding fluid.Recently it has been reported that modulating the laser power at the parametric resonant frequency in an overdamped system increased the amplitude of mean squared fluctuations [8]. However, these findings have been difficult to reproduce and are in strong contrast with the prediction of Langevin dynamics [9,10,11].…”
mentioning
confidence: 48%
“…While it is quite possible that some kind of instrumental noise could give rise to this effect, it is unlikely that the effect would show a linear variation with laser power as shown in Fig. 3 of the original Letter [1]. However, we cannot rule out a systematic source for the observation until we do more controlled experiments with and without an AOM.…”
mentioning
confidence: 92%
“…In regards to the experimental work of Deng, Forde, and Bechhoefer, the only difference is that the trap modulation is done via direct current modulation, rather than by use of an AOM as in the original experiment [1]. At first glance, this appears unimportant, and indeed it was mentioned in the Letter that the use of direct current modulation should also work.…”
mentioning
confidence: 99%
See 1 more Smart Citation